Long-term dynamics of the levels of anti-SARS-CoV-2 S-protein IgG antibodies in vaccinated individuals - O. M. Drapkina; S. A. Burns; A. Yu. Gorshkov; V. N. Shishkova; L. N. Ryzhakova; O. A. Litinskaya; A. A. Ivanova; A. V. Veretennikova; V. S. Bashnyak; E. Yu. Tatarevich (Кардиоваскулярная терапия и профилактика)
In the context of the ongoing coronavirus disease 2019 (COVID-19) pandemic, it is extremely important to study immunogenicity and immune response duration in different vaccines.Aim. As part of a prospective observational study, to study the levels of anti-SARS-CoV-2 S-protein IgG antibodies in individuals vaccinated with the Gam-COVID-Vac and CoviVac vaccines.Material and methods. The data of 93 people who completed the first 3 visits were analyzed, 23 of whom were vaccinated with the Gam-COVID-Vac vaccine and 70 people — with the CoviVac vaccine. We collected blood before the injection of vaccine doses I and II, as well as 42 days after the injection of dose I in order to quantitatively determine IgG levels. The level of anti-SARS-CoV-2 S-protein IgG antibodies was determined using the SARS-CoV-2 IgG ELISA-BEST reagent kit on the InfiniteF50 TECAN system.Results. A significant increase in anti-SARS-CoV-2 S-protein IgG antibodies was observed in those vaccinated with Gam-COVID-Vac. In the group of CoviVac vaccine, an increase in the level anti-SARS-CoV-2 S-protein IgG antibodies in absolute values was recorded, however, this increase did not reach statistical significance.Conclusion. The data obtained show that the level of anti-SARS-CoV-2 S-protein antibodies 42 days after Gam-COVID-Vac vaccination is significantly higher than after CoviVac vaccination. However, an increase in the level of IgG in both groups indicates the ability of both vaccines to stimulate the production of anti-SARS-CoV antibodies.